Living in a car-free housing development. Motivations and mobility practices of residents in nine developments in Switzerland and Germany. - Baehler, Daniel (My University, 2019)
Cars and the system of infrastructures and urban forms built to support them have many negative impacts such as pollution, greenhouse gas emissions and a high land use, particularly in cities. In response to this, car-free housing developments have emerged in different Western European cities. In these real-world laboratories of a mobility transition, residents commit to living without a private car in the long term. To overcome a car-centred society, it is important to understand why some households choose to voluntarily live car-free and move to these developments, and how they are mobile. This thesis represents the first large-scale study of car-free housing residents. It analysed nine developments, five in Switzerland (Burgunder in Bern, FAB-A in Biel/Bienne, Giesserei in Winterthur, Oberfeld in Ostermundigen and Sihlbogen in Zurich) and four in Germany (Klein Borstel and Saarlandstraße in Hamburg, Stellwerk60 in Cologne and Weißenburg in Münster). These sites include a diversity of car-free developments in terms of different dwelling types (even though six of them represent forms of collaborative housing), sizes, ages and localisations. A mixed methods approach was adopted to study the residents’ profiles, motivations and practices as well as their evaluation of the spatial and social context necessary to live car-free. A self-administered questionnaire survey (n=500) carried out in all nine developments was combined with in-depth interviews (n=50) conducted in six of them. The analyses show that the residents have very particular profiles. They have a high level of education and ethical or altruistic values are very important to them. Nearly half of the households are families. Almost all of them live deliberately without a private car and this does not represent a sacrifice for them. Their motivations for living car-free refer mainly to a combination of practical and personal reasons. The first type of motivation includes no need for a car and the availability of alternative transport modes, the second mainly revolves around ecological motivations. Conversely, the affordability of a car as well as health or age reasons are of very little importance. The motivations to move to a car-free housing development are similar, practical reasons such as the accessibility of the location are highlighted, but social aspects such as living in a community are important, too, particularly in the cooperative housing projects. The analyses of the residents’ mobility capital and practices revealed four types of strategies how to be mobile without owning a private car. First, car-free housing residents rely on (augmented) alternative transport modes, i.e. the bicycle (with a trailer or as an e- or a cargo bike), public transport and walking. Second, they use mobility and transport services, including taxis and delivery services, but also limited use of (carsharing or other borrowed) cars. Furthermore, digitalisation facilitates car-free living, especially smartphone apps allowing access to all mobility forms and supporting their use. Third, the inhabitants favour car-less accessibility and, thus, proximity often influences the localisation of their everyday activities. Fourth, the community of car-free residents appeared important, too. On a practical level, neighbourly help or common activities in the development facilitate car-free living, but, beyond that, the community also empowers the residents and “normalises” this way of life. Despite clear general tendencies for motivations and practices, an important diversity of car-free residents exists. A typology of lifestyles allowed us to uncover them. Based on their values and motivations to live car-free as well as on their mobility practices, six lifestyles of car-free residents were found: ecological, pragmatic and utilitarian cyclists and the same three types of multimodals, ecological, pragmatic and utilitarian. Finally, a certain spatial and social context is also necessary to live car-free. On the one hand, it consists of transport and other infrastructures such as local supply or spaces for common activities in the development. On the other hand, it includes immaterial aspects, particularly social norms allowing to consider car-freeness. In brief, a system of car-free mobility needs to be set up to overcome automobility. It consists of various individual strategies, but also of a spatial and social context allowing car-free living.

Autos und das für sie aufgebaute System an Infrastrukturen haben viele negative Auswirkungen, wie Schadstoff- und Treibhausgasemissionen und einen hohen Bodenverbrauch, insbesondere in Städten. Als Antwort darauf sind in verschiedenen westeuropäischen Städten autofreie Wohnsiedlungen entstanden. In diesen Reallaboren einer Mobilitäts-Transformation verpflichten sich die Bewohner*innen dazu, langfristig ohne eigenes Auto zu leben. In der Arbeit werden Bewohner*innen von neun autofreien Siedlungen befragt (fünf in der Schweiz: Burgunder in Bern, FAB-A in Biel, Giesserei in Winterthur, Oberfeld in Ostermundigen und Sihlbogen in Zürich und vier in Deutschland: Klein Borstel und Saarlandstraße in Hamburg, Stellwerk60 in Köln und Weißenburg in Münster. Untersucht werden die unterschiedlichen Arten von autofreien Wohnsiedlungen bezüglich Wohnform (Genossenschaften oder Wohnprojekte), Grösse, Alter und Lage. Ein Mixed-Methods-Ansatz wird angewandt um die Profile, Motivationen und Praktiken der Bewohner*innen zu erforschen, sowie deren Einschätzung des notwendigen räumlichen und sozialen Kontexts um autofrei zu leben. Die Resultate zeigen, dass die Bewohner*innen sich durch sehr spezifische Profile auszeichnen. Sie verfügen über ein hohes Ausbildungsniveau und ethische oder altruistische Werte sind ihnen am wichtigsten. Beinahe die Hälfte der Haushalte sind Familien. Fast alle von ihnen leben freiwillig ohne eigenes Auto. Ihre Motivationen autofrei zu leben beziehen sich hauptsächlich auf eine Kombination aus praktischen und persönlichen Gründen. Praktische Gründe wie die Erreichbarkeit der Lage der Siedlung werden hervorgehoben, aber auch soziale Aspekte wie das Gemeinschaftsleben, insbesondere in den Genossenschaften. Die Analysen des Mobilitätskapitals und der Mobilitätspraktiken der Bewohner*innen zeigen verschiedene Arten von Strategien, die ihnen ermöglichen, ohne eigenes Auto mobil zu sein. Darüber hinaus braucht es auch einen räumlichen und sozialen Kontext, um autofrei zu leben. Einerseits besteht dieser aus Verkehrs- und anderen Infrastrukturen wie Nahversorgung oder Räumen für Gemeinschaftsakti- vitäten in der Siedlung. Andererseits beinhaltet dieser aber auch immaterielle Aspekte, insbesondere soziale Normen welche ermöglichen, Autofreiheit in Betracht zu ziehen. Zusammengefasst muss ein System von autofreier Mobilität aufgebaut werden, um die Automobilität zu überwinden. Es besteht aus vielfältigen individuellen Strategien, aber auch aus einem räumlichen und sozialen Kontext, der autofreies Leben ermöglicht.
In einer autofreien Siedlung leben. Motivationen und Mobilitätspraktiken der Bewohner*innen neun autofreier Wohnsiedlungen in der Schweiz und Deutschland.
Keywords: Individualverkehr; Verkehrsinfrastruktur; Autofreie Siedlung; Autofreies Wohnen; Studie; Wohnsiedlung; Wohnform; Bevölkerungsstruktur; Sozialstruktur; Mobilitätsverhalten; Autofreiheit; Lebensstil; Infrastrukturangebot; Erreichbarkeit; Reallabor